Festive clothing and national costumes in 20th century East Greenland - Buijs, Cunera; Petersen, Mariane (Études/Inuit/Studies, 2004)
AbstractThis study on developments in festive clothing is based on clothing and photograph collections in museums, interviews with Tunumiit (East Greenlanders) and participant observation during several months in Kalaallit Nunaata Tunua (East Greenland) in 1997, 1998 and 2001. Festive garments for special occasions did not exist in the traditional pre-Christian culture of East Greenland. In this article we investigate what influences affected the development of special clothing for festive occasions. Changes in Kalaallit Nunaata Kitaa (West Greenland) and European influences deeply affected clothing traditions in East Greenland. In the course of this process, some Tunumiit garments came to disappear and others were re-invented and re-shaped using new materials. Preparing animal skins and sewing attire always have been a women's preserve. In the past, sewing qualities were highly valued within Inuit society. Today, sewing skills and designing clothing are paid for but they still reflect women's qualities and sealskin garments shape Kalaallit identity. The development of festive clothing and the continuity in celebrating first events and rites of passage testify to the dynamics and strength of East Greenland culture. East Greenland clothing is part of a vivid cultural tradition and is still “women's magic.”